ANALYSIS QUALITY OF SERVICE OF INTERNET NETWORK FIBER TO THE HOME SERVICE PT. XYZ USING WIRESHARK - Daffa Aditya Rachman; Yusuf Muhyidin; Muhamad Agus Sunandar (Universitas Lampung, 2023)
The development of information technology continues to grow every year and successfully creates new technology, namely the internet. The internet is a public computer system that is globally connected and uses TCP/IIP as a packet-switching communication protocol. Telecommunication companies have access to internet networks, namely Fiber to the home (FTTH). FTTH provides services so that customers can utilize optical telecommunications. So that it will have a larger bandwidth to access the telephone, internet, and cable TV at the same time. In the service that has been done by xyz company, there have been many users who use this service, but there are several factors in the service regarding the slow and poor internet network at certain hours, and it does not answer how the solution to overcoming FTTH services from xyz company in the field of physical network This research was conducted using the Quality of Service (QoS) method to overcome these problems by using four parameters of QoS: throughput, packet loss, delay, and jitter. QoS is the collection of a network to provide data traffic services that pass through it. The results found that the quality of service on 5 SSIDs/xxyz company customers with a speed of 20 MbpsThe results are